2008
DOI: 10.1051/0004-6361:20078436e
|View full text |Cite
|
Sign up to set email alerts
|

Accurate early positions for Swift GRBs: enhancing X-ray positions with UVOT astrometry

Abstract: The Swift Gamma Ray Burst satellite routinely provides prompt positions for GRBs and their afterglows on timescales of a few hundred seconds. However, with a pointing accuracy of only a few arcminutes, and a systematic uncertainty on the star-tracker solutions to the World Coordinate System of 3-4 arcseconds, the precision of the early XRT positions is limited to 3-4 arcseconds at best. This is significant because operationally, the XRT detects >95% of all GRBs, while the UVOT detects only the optically bright… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…We derive astrometrically corrected X-ray positions by using the XRT-UVOT alignment and matching to the U-SNO-B1 catalog (Monet et al, 2003) as described in Goad et al (2007) and Evans et al (2009) 3 . Fig.…”
Section: Data Reductionmentioning
confidence: 99%
“…We derive astrometrically corrected X-ray positions by using the XRT-UVOT alignment and matching to the U-SNO-B1 catalog (Monet et al, 2003) as described in Goad et al (2007) and Evans et al (2009) 3 . Fig.…”
Section: Data Reductionmentioning
confidence: 99%
“…14 After correcting the XRT astrometry following Goad et al (2008), we identified a bright point source at (J2000.0) coordinates α = 20 h 58 m 19. s 85, δ = +05…”
Section: X-raysmentioning
confidence: 99%
“…The uncertainties in the techniques listed above are dominated by two components: photon statistics, and the uncertainty in the star tracker solutions, which imposes a lower limit of about 3 arcseconds on the XRT position accuracy. We have recently developed a technique 14 that eliminates the latter (star tracker) component by using the UVOT instrument as a "super star tracker", taking advantage of the precise registration achievable between UVOT images and astrometric star catalogs, and of the highly stable Swift Optical Bench, which maintains the relative alignment between the XRT and UVOT boresights to better than an arcsecond in flight. We achieve additional improvements by using a fitting routine to determine XRT source positions in detector coordinates that accounts for the instrument PSF and that correctly and accurately treats the effects of bad pixels and columns.…”
Section: Astrometric Positionsmentioning
confidence: 99%
“…In these figures we have simply plotted the difference between the best X-ray and optical positions. Testing of this technique using bursts with UVOT afterglows shows that 90% of the XRT positions are within 2 arcseconds of the UVOT position 14 .…”
Section: Astrometric Positionsmentioning
confidence: 99%